Prevalence of pre-diabetes in adolescents aged 11-17 years with high risk factors - Balamurugan, Kuppan; Ponprabha, Rajangam; Sivashankari, Veeramani (International Journal of Research in Medical Sciences, 2021)
Background: Obesity is a rising global epidemic in children which leads to pre-diabetes and overt diabetes. Identification at early stage helps in early intervention. This study was undertaken to study the prevalence of pre-diabetes in urban school going adolescents aged 11-17 years with high risk factors. Methods: This was a prospective cross-sectional study conducted in Chennai, India between December 2011 and November 2012. Overweight or obese adolescents in the age group 11-17 years, either with family history of diabetes or acanthosis nigricans or both were included. After obtaining informed consent from parents, history was obtained in pre-tested questionnaire. Results: 148 adolescents were enrolled in the study (n=148), 71.62% were females, mean weight was 59.54±10.44 kg, mean height was 150.92±8.62 cm, mean BMI was 26.19±3.23 and mean blood glucose was 82.1 mg/dl. 60.81% of subjects were overweight and others obese. Girls had statistically significant higher mean weight and mean BMI than boys. 78.37% had acanthosis nigricans, 47.29% had family history of diabetes, 12.16% had pre-diabetes and the mean blood glucose in pre-diabetics was 104.9 mg/dl. Pre-diabetes was higher in adolescents with family history of diabetes (p=0.038). Conclusions: Recognition of risk of type 2 diabetes in the asymptomatic pre-diabetes phase needs to be emphasized and targeted screening of high risk children for pre-diabetes seems to be justified. The morbidity and mortality of youth onset type 2 diabetes can be reduced only by early detection and treatment.